Risk perceptions in Japanese SMEs: the role of Internet marketing capabilities in firm performance. (3rd October 2019) - Mathews, Shane W.; Maruyama, Masahiro; Sakurai, Yuka; Perks, Keith J.; Sok, Phyra
Abstract: Internet plays a very important role for the success of small- and medium-sized enterprises (SMEs). Many Japanese SMEs are risk-averse in adopting technological innovation such as the Internet. Others, despite these risk-related business norms, recognize the importance of technology and develop and deploy Internet marketing technology to compete in the current competitive environment. Drawing upon these contradicting practices among Japanese SMEs, this study investigates how Japanese SMEs risk perception impacts on the deployment of Internet marketing capabilities, the relationships between perception of risk, international mind-set, business networks, Internet marketing capabilities, and firm performance. This study makes two contributions. Firstly, there has been limited research investigating how Internet-related capabilities impact on firms' performance. Secondly, there are few Internet-related studies in Japan. Thus, our emphasis on key antecedents and outcomes of Internet marketing capabilities among Japanese SMEs contributes significantly to our understanding of this unique contextual setting. The findings also provide some insights to managers/owners of Japanese SMEs that lower risk perception fosters adoption of the Internet and combined with other resources creates Internet marketing capabilities which results in higher performance.